A generic framework for consultancy services pricing in Ghana: the case of quantity surveying practice - Adesi, Michael (2015)
Thesis submitted to the Department of Building Technology of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of a Master of Philosophy (MPhil) degree in Building Technology,